2021
DOI: 10.3390/ijerph18105253
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Peritraumatic Distress as a Function of Age and Gender in a Spanish Sample

Abstract: The sudden outbreak of the COVID-19 pandemic has profoundly altered the daily lives of the population with dramatic effects caused not only by the health risks of the coronavirus, but also by its psychological and social impact in large sectors of the worldwide population. The present study adapted the COVID-19 Peritraumatic Distress Index (CPDI) to the Spanish population, and 1094 Spanish adults (mean age 52.55 years, 241 males) completed the Spanish version in a cross-sectional online survey. To analyze the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 38 publications
13
34
0
1
Order By: Relevance
“…Again, with regard to sex differences, the findings showed that boys had higher externally oriented thinking than girls. This result is in line with our hypotheses and several studies that found higher levels of alexithymia [ 131 ] and specifically of externally oriented thinking in male youths [ 132 ]. In this context, in accordance with the normative male alexithymia hypothesis posited by Levant [ 133 , 134 ], and supported by the recent scientific literature [ 135 ], males may be inclined to show more alexithymic traits than females due to gender-related social pressure, implying that males should not freely express difficult or attachment feelings.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Again, with regard to sex differences, the findings showed that boys had higher externally oriented thinking than girls. This result is in line with our hypotheses and several studies that found higher levels of alexithymia [ 131 ] and specifically of externally oriented thinking in male youths [ 132 ]. In this context, in accordance with the normative male alexithymia hypothesis posited by Levant [ 133 , 134 ], and supported by the recent scientific literature [ 135 ], males may be inclined to show more alexithymic traits than females due to gender-related social pressure, implying that males should not freely express difficult or attachment feelings.…”
Section: Discussionsupporting
confidence: 93%
“…Another possible explanation could be the fact that, as suggested by Bangasser et al [ 129 , 130 ], female gender represents a biological factor commonly associated with greater psychological vulnerability in the face of stressful life events, resulting in higher peritraumatic symptoms compared to males [ 131 ]. In line with our findings and the studies by Bonati et al [ 51 ] and Jiménez et al [ 132 ], this greater vulnerability to stress-related psychopathological sufferance has also been confirmed in relation to symptoms of peritraumatic distress due to COVID-19.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…With regard to sex, being male has shown to be a protective factor for peritraumatic distress, and this is consistent with the existing literature ( Al-Hanawi et al, 2020 ; Bonati et al, 2021 ; Gloster et al, 2020 ; Jiménez et al, 2021 ; Kafle et al, 2021 ; Marzo et al, 2021a , 2021b ; Qiu et al, 2020 ; Shrestha et al, 2020 ). Numerous studies have also shown a higher prevalence of symptoms of depressive and anxious spectrums in women ( Ribeiro et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…Multivariate logistic regression revealed protective factors in age>35, the malesex, higher educational level, night sleep hours >7, and being physically active. Regarding the role of age, previous evidence revealed controversial results ( Parlapani et al, 2021 ), with some studies showing old age as a risk factor for peritraumatic distress ( Qiu et al, 2020 ; Shrestha et al, 2020 ), while other studies identified it as a protective factor ( Al-Hanawi et al, 2020 ; Costantini and Mazzotti, 2020 ; Gloster et al, 2020 ; Jiménez et al, 2021 ; Ramasubramanian et al, 2020 ), or did not find any significant association with age ( Megalakaki et al, 2021 ). A possible explanation for the decrease in the risk of peritraumatic distress with advancing age could be the greater knowledge of the older population with respect to epidemic events.…”
Section: Discussionmentioning
confidence: 99%